ARTYKUŁ PRZEGLĄDOWY/REVIEW PAPERExcitatory amino acids and rheumatoid diseases - Parada-Turska, Jolanta (Reumatologia/Rheumatology, 2005)
Excitatory amino acid (EAA), glutamate is a major neurotransmitter in the central nervous system. Its role in the periphery remains mostly unknown. Recently, EAA receptors there found on peripheral sensory terminals and dorsal root ganglion cells implicating their involvement in sensory and nociceptive transduction. The involvement of EAA mechanisms in inflammation was also suggested. It can be speculated that the use of EAA antagonists may provide a novel alternative for pharmacological intervention in joint inflammation and pain.